Series, series, series. More series, please (Journal of Parents and Teachers, 2014)
TV series play a fundamental role in the personal and social development of children, so it is necessary to teach our students to be critical viewers of all types of series. In order to know more about this genre of the small screen, the article analyzes the types of series, the most viewed ones, and their best episodes.
Keywords: TV series; critical viewers.